Chances and discrimination in dual vocational training of refugees and immigrants in Germany - Rusert, Kirsten [Verfasser]; Stein, Margit [Verfasser] (My University, 2023)
"This article depicts the obstacles within the vocational education for trainees with escape and migration experience in Germany. The structure of the highly formalised vocational training system in Germany is based on the assumption of a ‘normal case’ of an educational biography. However, this neither applies to the often-broken educational pathways of refugees and immigrants, nor to an increasing number of young people without migration experience. Access to training is largely organised by the private sector, and so, applicants outside the classic profile are often disadvantaged both in access and in the learning processes within the training. The article focuses on the challenges of trainees with escape and migration experience in vocational schools as part of dual vocational training, and discusses the extent to which these schooling structures are inclusive or discriminating. For this purpose, the results from interviews with young immigrants in training are evaluated." (Author's abstract ; BIBB-Doku)
Keywords: P 2.3 Auszubildende; T 3.4 Befragung; 370; Auszubildender; Migrant; Migrationshintergrund; Flüchtling; Ausbildungschance; Bildungsverlauf; Interview